Kampung MATFA : Otoritas Tuan Iman dan Budaya Komunal - Indah Fikria Aristy; Ichwan Azhari; Fikarwin Zuska (Universitas Negeri Medan, 2021)
This study describes the authority of Tuan Imam and the communal culture practiced in the Kampung MATFA (Majelis Taqlim Fardhu Ain) Langkat District of North Sumatra. This research uses qualitative research methods with data collection techniques through observation, interviews, and literature study. The results of this study indicate that the Kampung MATFA implements a communal system in its social, cultural and economic activities. In addition, there is no private ownership that is shared ownership based on spiritual teachings delivered by the leader. The conclusion in this study is that the leader of Kampung MATFA, Tuan Imam, has the authority to manage his congregation by building a communal culture in maintaining its existence as a charismatic leader and his congregation for survival.